Knockdown of PRDX2 sensitizes colon cancer cells to 5-FU by suppressing the PI3K/AKT signaling pathway. Issue 3 (11th May 2017) - Xu, Jun; Zhang, Shouru; Wang, Rong; Wu, Xingye; Zeng, Li; Fu, Zhongxue
Abstract : Although, 5-Fluorouracil (5-FU) remains widely used in adjuvant therapy in patients with colon cancer, resistance to 5-FU-based chemotherapy is an important reason for treatment failure. Recent studies have reported that an enhanced reactive oxygen species (ROS) scavenging system shows drug resistance to 5-FU. Peroxiredoxin-2 (PRDX2), is an important member of the ROS scavenging system, and may be a potential target that promotes chemosensitivity to 5-FU in colon cancer. Here, we depleted PRDX2 by PRDX2-shRNA-LV transduction in two colon cancer cell lines and found that in vitro PRDX2 knockdown facilitates cell death, and apoptosis in 5-FU-treated colon cancer cells. In addition, we found that PRDX2 depletion in mice treated with 5-FU resulted in, inhibition of tumor growth, compared with mice treated with 5-FU alone. Our data also suggested that the PI3K/AKT signaling pathway links PRDX2 with 5-FU-induced apoptosis in colon cancer. Furthermore, when PRDX2 was overexpressed in colon cancer cells, we found increased p-AKT protein expression and reduced Bcl-2/Bax protein expression. PRDX2 and p-AKT protein expression were analyzed by immunohistochemistry technology in human colon carcinoma tissues. Pearson correlation coefficient is 0.873 and P <0.05. PRDX2 depletion led to reduced p-AKT expression and PI3K/AKT pathway inhibition promoted cell apoptosis in HT29 cell line. Taken together, our study suggests that decreasing the expression of PRDX2 could be a promising strategy for increasing the sensitivity of colon cancer cells to 5-FU.